Functional Optical Plasmonic Resonators Fabricated via Highly Photosensitive Direct Laser Reduction. Issue 4 (20th December 2015) - Tabrizi, Sahar; Cao, Yaoyu; Cumming, Benjamin P.; Jia, Baohua; Gu, Min
Abstract : Functional optical plasmonic resonators are fabricated through a simple, low‐cost, two‐photon photoreduction method. The silver c‐shape array has a highly conductive structure with an extremely smooth surface in addition to high‐resolution features. These functional resonators are polarization responsive and readily tunable in a large dynamic range by simply changing the laser fabrication parameters.